Analisis Penggunaan Media Pembelajaran Berbasis Media Visual Terhadap Hasil Belajar Bahasa Indonesia Siswa - Dila Rizki Amanda (Lembaga Pengembangan Kinerja Dosen, 2024)
The focus of this research is to investigate the influence of visual learning media on students' Indonesian language learning outcomes. The aim is to reveal the use of YouTube as an Indonesian language learning tool, explore students' perceptions of using Kahoot (a game-based learning application), describe the impact of using Quizizz on student motivation and learning outcomes, and analyze the e-learning learning process via the Edmodo platform in subjects Indonesian. It is also believed that the use of this media can increase students' interest in reading and stimulate the development of their ideas. With stimulated ideas, students' thinking abilities, especially higher level thinking, can be improved directly. In this rapidly developing era, the role of teachers is increasingly vital in the world of education. They are expected to actively develop insight and skills, including in the use of learning media. Visual media is an effective tool in learning, helping students understand the material better. Therefore, it is important for teachers to continue to innovate in creating learning media that suits the needs of the subjects being taught, in order to increase learning effectiveness and student engagement.